The utilitarian and hedonic factors affecting the proneness to buy 99-ends products among consumers - Uthayabanu Govindasamy, 1992-; Thoo, Ai Chin; Fakulti Pengurusan 538641 (2016)
Project Paper (Sarjana Muda Pengurusan (Pemasaran)) - Universiti Teknologi Malaysia, 2016